PERAN DPR DALAM MENJALANKAN KONTROL DEMOKRATIS ATAS PEMBARUAN SEKTOR KEAMANAN - Poltak Partogi Nainggolan (Sekretariat Jenderal DPR RI, 2011)
Reform movement has not not only brought down the Soeharto authoritarianregime but also strengthened Indonesian people’s pressure for better militaryreform and parliamentary role. As parts of democratic transition, the reforms of both state institutions started with the amendments of constitution. Afterward, DPR becomes a ‘superbody,’ and the pressure for security sector reform (SSR) was further conducted. These studies revealed that parliament’s strong position still, however, in reality could not comprehensive- and significantly push SSR as has been previously voiced by the reform movement.